Analisis Teologi Kesehatan Tentang Pandemi Virus Covid-19 Perspektif Al-Qur’an - Rahmanto, Oki Dwi; Manto, Charis (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
The Covid-19 virus pandemic is still developing in Indonesia. Even though the government has tried to reduce activities to suppress the increase in Covid-19 cases. Of course, it is necessary to pay attention so that this case ends quickly. By referring to the Qur'an about health, it is hoped that it can be an illustration of how the solution of the Qur'an responds to Covid-19. This type of writing is library research, namely data taken from journals, dictionaries or interpretations related to research such as the interpretation of Ibn Kathir. The method taken is descriptive-analysis, where the researcher describes the history or epidemics that have occurred in the Qur'an and then proceeds to analyze health theology according to the Qur'an. The results found were, first, the Qur'an views health in order to deal with Covid-19 such as maintaining cleanliness, always obeying the government, eating healthy food and maintaining psychological conditions in order to reduce stress levels